The Relationship Of Gadget Use With The Language Development Of 2-5 Year-Old Children In Buleleng - Desak Ketut Sugiartini; Dewi Aprelia Meriyani (HealthCare Nursing Journal, 2023)
The use of gadgets by toddlers can hinder their growth and development, because toddlers are the most important period in increasing optimal growth and development of children because they can influence and determine the future development of children. The purpose of this study was to determine the relationship between the intensity of gadget use and the developmental aspects of toddlers aged 2-5 years in Tinga-tinga Village. This research uses the type of analytic research in the form of observational. The experimental design used in this study is a cross-sectional research design. The sample in this study were children aged 24-60 months in Tinga-tinga Village, totaling 68 people. The sampling technique uses total sampling, the independent variable is the intensity of using gadgets and the dependent variable is the development of aspects of speech and language. The data analysis technique used is chi square analysis of the closeness of the relationship between the two variables with the Cramer's v coefficient. From the analysis results obtained a p value of 0.000 and a correlation coefficient of 0.000162. This shows p <0.05, which means that there is a significant relationship between the intensity of gadget use and delay.